Role of Entrepreneurship Education Management in Creating Entrepreneurship Competitive Advantage in Students: Case Study on F-Clean Products at MA Al-Rahman Sukabumi - Rohmah, Siti; Paramarta, Vip; Mulyanti, Dety (Journal of Education Method and Learning Strategy, 2024)
Based on a preliminary study conducted by researchers, the F-CLEAN liquid soap company sells liquid soap products according to their use which can be delivered directly to consumers. However, researchers found a problem in the field, namely that entrepreneurship coaching was going well, but there were some students who still did not understand entrepreneurship. The aim of the research is to analyze the role of entrepreneurial education management in creating entrepreneurial competitive advantages for students at MA Al-Rahman Sukabumi. The research method uses a case study with a qualitative approach. Data collection techniques use interviews, observation and literature study. Data analysis using the NviVo 14 application. The research results show that entrepreneurship education management has a role in creating a competitive advantage in entrepreneurship for MA AL-RAHMAN Sukabumi students. The role of entrepreneurial management is to foster an entrepreneurial spirit in MA AL-RAHMAN Sukabumi students through entrepreneurship learning, business planning, direct practice of F-CLEAN (in the organizing section), implementation and evaluation. Meanwhile, the role of educational management is to create competitive advantage through the perspective of customer value (not easily imitated), having interest, self-confidence and the unique value of special F-CLEAN products. With the role of entrepreneurship education management, it is hoped that inhibiting factors such as students' lack of interest in entrepreneurship and being shy about starting a business can be overcome through entrepreneurship education management.